Examining the impact of audit committee characteristics on audit fees - Suhaimi, Muhammad Zharif; Hasnan, Suhaily; Mohd Khairuddin, Khairul Ayuni; S Jainal, Shariffah Hazirah; Ismail, Rina Fadhilah; Anderes, Gui (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This study examines the effects of various audit committee characteristics, including meeting frequency, size, gender diversity, school ties, and independence, on audit fees in Malaysia. Utilizing a sample of the top 100 companies listed on Bursa Malaysia from financial periods 2019 to 2023, the study employs multiple regression and correlation analyses, using the Statistical Package for the Social Sciences (SPSS) to interpret the data. The results reveal a significant negative relationship between audit committee school ties and audit fees, suggesting that personal affiliations within the audit committee may lower the perceived governance risk, potentially leading to cost reductions. Additionally, a positive and significant relationship is found between the frequency of audit committee meetings, size, and gender diversity, with audit fees. This suggests that audit committee that are more engaged, diverse, and structurally robust may enhance its oversight functions, leading to an increased scope and intensity of audit work, which in turn results in higher audit fees. Conversely, the study finds an insignificant negative relationship between audit committee independence and audit fees. This research findings supports the signalling theory and provides valuable insights for practitioners and policymakers on the trade-offs between strengthening audit committee oversight functions and managing their associated financial implications via elevated audit costs. Regulators may also consider reviewing existing governance guidelines to ensure that they encourage audit committee attributes that are most effective in promoting transparency and accountability.